MODELING OF THREE TOMATO VARIETIES UNDER MICROWAVE DRYING (FULafia Journal of Science and Technology, 2018)
Drying experiments of thin layer tomato samples were carried out by using microwave drying. The drying experiments were carried out at 120, 250, 420 and 520 W of microwave power. The drying rates increased with the increasing microwave power levels. There was a reduction in moisture content with increased drying time and microwave power while drying took place in the falling rate period. Dying processes were completed between 20 and 180 min for tomato samples depending on the microwave power level. All the three and four parameter models predicted well the drying characteristics of all varieties of tomato studied with R2 values greater than 0.99. The Demir and Midilii models were the best models selected based on R2, RMSE and Chi square values.
Keywords: Microwave drying; Modelling; Tomato; Diffusivity; Energy utilization